Decision-Making of Fredholm Operator on a New Variable Exponents Sequence Space of Supply Fuzzy Functions Defined by Leonardo Numbers (Contemporary Mathematics, 2024)
In this article, we will use a weighted regular matrix formed by Leonardo numbers and variable exponent sequence spaces to build a new stochastic space. We have proposed various geometric and topological structures for this new space, as well as the multiplication operator that operates on it.
Keywords: Leonardo numbers; variable exponent; extended s-fuzzy numbers; multiplication operator; non-newtonian fluids